2012
DOI: 10.1371/journal.pone.0044856
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Relaxin Signaling Pathway and Testicular Dysfunction in Mouse Offspring upon Maternal Exposure to Simazine

Abstract: Simazine is a triazine herbicide that is being widely applied worldwide and commonly detected in surface and groundwater. Despite its popular use in controlling weeds and algae, very limited information is available regarding its toxicity. In the present study, pregnant mice were orally exposed to low doses (0, 5, 50, or 500 µg/kg body weight per day) of simazine during gestation and lactation, during which no overt maternal toxic response was detected, and their offspring was assessed. Simazine-exposed male o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Studies have shown that acps are involved in immune, reproductive, digestive systems and apoptotic process (Bozzo et al 2002;Yoneyama et al 2004). Downregulated acps may play an important role in the simazine-induced adverse effects on the reproductive system observed in our study and other studies (Zorrilla et al 2010) as well as other genes such as Rxfp1 (Park and Bae 2012). We also found genes involved in endocrine functions including ptgs2, stc1 and th were downregulated.…”
Section: Resultssupporting
confidence: 79%
“…Studies have shown that acps are involved in immune, reproductive, digestive systems and apoptotic process (Bozzo et al 2002;Yoneyama et al 2004). Downregulated acps may play an important role in the simazine-induced adverse effects on the reproductive system observed in our study and other studies (Zorrilla et al 2010) as well as other genes such as Rxfp1 (Park and Bae 2012). We also found genes involved in endocrine functions including ptgs2, stc1 and th were downregulated.…”
Section: Resultssupporting
confidence: 79%
“…The shortened AGD observed in female neonates exposed maternally and lactationally to 5 g/kg/day (Table 2), suggests an estrogenic effect of simazine on female mice since AGD is a common and sensitive index of in utero exposure to EDs (McIntyre et al, 2001;Wolf et al, 2004). In a previous report, AGD was not significantly altered in male offspring by maternal exposure to simazine (Park and Bae, 2012), implying that female littermates are more susceptible to perinatal exposure of simazine at low doses at least as it relates to endocrine disruption. Zorrilla et al demonstrated that exposure to simazine (25-200 mg/kg/day) in female weaned littermates of Wistar rats delays vaginal opening (Tinfo et al, 2011), indicating an antiestrogenic effect of simazine.…”
Section: Discussionmentioning
confidence: 79%
“…1016/j.etap.2014.10.008 1382-6689/© 2014 Elsevier B.V. All rights reserved. disruption of the relaxin pathway (Park and Bae, 2012). Male rats exposed to simazine exhibited increased release of adrenocorticotropic hormone and corticosterone (Laws et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated to increase testicular oxidative stress, which leads to an increase in germ cell apoptosis and subsequent hypospermatogenesis (Turner and Lysiak, 2008). Regarding herbicide and heavy metal exposure during gestation and lactation, cadmium and simazine were found to interfere with the function of male reproductive system in offspring (Ji et al, 2011;Park and Bae, 2012).…”
Section: Discussionmentioning
confidence: 99%